Rede social digital e mobilização social : o Facebook nas manifestações de junho de 2013 - Santos, Roberto Teixeira dos (2016)
This research aims to investigate the ways of appropriation of digital social networks in countervailing mobilizations. The study of the case is the movement “Is not for 20 cents, it‟s for the rights", on the social networking site Facebook, on the occasion of the protest movements in mid-2013 in Espirito Santo, Brazil. In addition to the literature review about the network society, internet, digital social networks and social movements in the present days, the survey is based on contents of studies published on Facebook, in interviews with key mediators of online community page in question.